2014
DOI: 10.1016/j.celrep.2014.03.027
|View full text |Cite
|
Sign up to set email alerts
|

TSPAN2 Is Involved in Cell Invasion and Motility during Lung Cancer Progression

Abstract: In lung cancer progression, p53 mutations are more often observed in invasive tumors than in noninvasive tumors, suggesting that p53 is involved in tumor invasion and metastasis. To understand the nature of p53 function as a tumor suppressor, it is crucial to elucidate the detailed mechanism of the alteration in epithelial cells that follow oncogenic KRAS activation and p53 inactivation. Here, we report that KRAS activation induces epithelial-mesenchymal transition and that p53 inactivation is required for cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…Genes that are derepressed by the down-regulation of p53, such as MDR1 (37), CD44 (38), TCTP (39), and TSPAN2 (40), have been identified, and we found that TSPAN12 was derepressed by the down-regulation of p53 in fibroblasts. The mechanism underlying the transcriptional derepression of TSPAN12 through the down-regulation of p53 is complex, and even though a reporter assay using the TSPAN12 promoter region (−1,000 to −1) and ChIP analysis of the proximal TSPAN12 promoter region (−230 to −1) using various specific primers were conducted, we could not confirm that TSPAN12 was a direct p53-target gene.…”
Section: Discussionmentioning
confidence: 88%
“…Genes that are derepressed by the down-regulation of p53, such as MDR1 (37), CD44 (38), TCTP (39), and TSPAN2 (40), have been identified, and we found that TSPAN12 was derepressed by the down-regulation of p53 in fibroblasts. The mechanism underlying the transcriptional derepression of TSPAN12 through the down-regulation of p53 is complex, and even though a reporter assay using the TSPAN12 promoter region (−1,000 to −1) and ChIP analysis of the proximal TSPAN12 promoter region (−230 to −1) using various specific primers were conducted, we could not confirm that TSPAN12 was a direct p53-target gene.…”
Section: Discussionmentioning
confidence: 88%
“…In these cells, elevation of ROS levels has been shown to promote proliferation and enhance motility and invasion [18,19]. Reciprocally, antioxidants have been for a long time considered as tumor suppressing agents [20-24]. However, recently the opposite functions of antioxidants have been reported.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Accordingly, overproduction of ROS was identified as an inhibitor of tumor cell proliferation, viability and various transformed phenotypes [20-24;33-36]. The latter effects of ROS caused significant attention to the mechanisms regulating their production and utilization in cancer cells [35,36], and the potential exploitation of these mechanisms in novel antineoplastic agents [37].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In malignancy, strong expression of Tspan2 is associated with poor prognosis in lung cancer and it has been linked to disease progression associated with p53 inactivation [77]. Mutation of the tumour suppressor p53 is often observed in invasive tumours and contributes towards cancer metastasis by modulating EMT [78].…”
Section: Tspan2 and Cancer Progressionmentioning
confidence: 99%
“…Knockdown of Tspan2 reduced invasiveness and motility in p53-depleted SAECs or cancer cell lines with p53 mutations, whereas overexpression of Tspan2 enhanced these attributes. Knockdown of Tspan2 was also shown to reduce lung metastasis in a mouse model [77]. Co-immunoprecipitation identified CD44 as one of the proteins interacting with Tspan2 and the role of this protein, which is known to interact with other tetraspanins, was investigated further.…”
Section: Tspan2 and Cancer Progressionmentioning
confidence: 99%